2014
DOI: 10.1371/journal.pone.0106600
|View full text |Cite|
|
Sign up to set email alerts
|

ERCC1 Single Nucleotide Polymorphism C8092A, but Not Its Expression Is Associated with Survival of Esophageal Squamous Cell Carcinoma Patients from Fujian Province, China

Abstract: Esophageal carcinoma is one of the world's deadliest cancers. Esophageal squamous cell carcinoma (ESCC) is more frequent than adenocarcenoma (AC) in China. Platinum-based chemotherapy with surgical resection is a common treatment approach for ESCC; however, the treatment response is uncertain. Evidence suggests polymorphisms in genes encoding excision repair cross-complementing group 1 (ERCC1), a protein involved in nuclear excision repair (NER), may help predict response to cisplatin and other platinum-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Late treatment leads to a poor prognosis, with 5-year survival rates of only 15% to 25%. [13] A poor prognosis is usually due to recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Late treatment leads to a poor prognosis, with 5-year survival rates of only 15% to 25%. [13] A poor prognosis is usually due to recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identification of molecular index predicting drug sensitivity may help to guide the application of EC. Polymorphism of Excision Repair Cross-Complementing 1 (ERCC1) gene is correlated with treatment efficacy using platinum drug in EC patients [21]. However, few studies have been performed regarding the correlation between XRCC1, XPD and GSTP1 gene and platinum drug efficacy against EC.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiologic studies have reported that ERCC1 polymorphisms may influence the outcome of cisplatin treatment in gastric cancer, non-small cell lung cancer (NSCLC), ovarian cancer, and esophageal squamous cell carcinoma (Qi et al, 2013;Chen et al, 2014;Gao et al, 2014;Liu et al, 2014). Liu et al (2014) conducted a cohort study to investigate the role of ERCC1 gene polymorphism in response to chemotherapy and clinical outcome in gastric cancer, and did not find the ERCC1 rs3212986 polymorphism to be associated with OS in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al (2014) also conducted a cohort study to investigate the role of three SNPs of ERCC1 in the clinical outcome of NSCLC, and found that the TT genotype of ERCC1 rs11615 and the AA genotype of rs3212986 polymorphisms were associated with increased risk of death from NSCLC. Chen et al (2014) showed that the ERCC1 rs3212986 polymorphism showed a significant association with survival in epithelial ovarian cancer patients. However, another study found that ERCC1 rs3212986 did not produce a significant difference in the response to chemotherapy or overall survival in ovarian cancer (Qi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%